Challenges of the early childhood education teacher in the context of the Covid-19 pandemic (Research, Society and Development, 2022)
The closing of schools due to the need for social isolation in the fight against the spread of Covid-19 made managers, teachers, parents and students review teaching and learning methods, accept the challenges that were imposed and reinvent themselves and methodologies. to continue the education process. Now, the scenario for presenting the program content to be presented to students was no longer the classroom, but the teacher's residence. How to adapt the new work environment to the old task of teaching? Teachers were affected by all the transformation that the pandemic incited not only in education, but in all areas of activity. Bringing the new model of remote work to the domestic routine was challenging, as there was no longer the presence of the blackboard or desks for the class to be taught. Faced with this new situation, the following question arose: What are the main challenges that the early childhood education teacher experienced during the Covid-19 pandemic? The present study sought publications that would substantiate the clarification of the challenges and present solutions for overcoming them.